Aids research: adhesion difficulty for HIV-negative individuals - Santos, Fernanda P.; Machado, Alcyone A. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Toe communication moment of lhe serological diagnosis for the infcction by lhe Human lmmunodeficiency Virus (HlV) appcars as a "dealh sen1ence" fonn whal could promote depression. fcar of a chronic diseasc. physical and mental debilitation and lhe terror of suffering a premature death. Objectifying 10 analyze the causes of 1he non-adhesion and the difficulties of lhe panicipanls of a study on lhe psychological aherations and life quali1y. this work was done in Toe Testing and Counseling Cenlerof lhe Municipal Depanment of Heahh in Ribeirão Pre10-SP. through lhe questionnaire applica1ion WHOQOL- 100 ai lhe moment of lhe first serological cxam and 6 months afler lhe diagnosis of presence or no1 of antibodies against HIV. The instrument is made up or 100 questions in a scale of Liken type answers. delined by six domains and 24 facets. A significant number of HIV-Negative individuais (39/90-43.3%) didn't allend, however lhey have becn conlacted. Twenty-five have verbally confirmed lhe not disposition 10 collaboratc with lhe research, which 8 were scheduled forotherdale and didn't altcnd. Six of the individuais (6,6%) didn't auend because oftransponation difficuhy and 8 (8,8%) were nol found. We conclude that: control and prevemion programs should consider lhe population panicularities. especially stigmas and prejudices; professionals of health musl be prepared for a beuer interaction with lhe population aimed; teams for HIV/Aids prevcntion must be muhidisciplinary and promised 10 stimula1e lhe changc of behavior : clients must be reminded of responsibilities fron1 10 their health.